Publication Trend of Environmental Topics in The Journal of Biological Education in Indonesia (Sinta 2; 2017-2021): A Systematic Literature Review - Rahardjanto, Abdulkadir; Husamah, H. (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
Environmental issues and accompanying problems need to be discussed. However, there has been no systematic literature review (SLR) that focuses on environmental topics. This SLR aims to publish trends in environmental topics in biology education journals in Indonesia, focused on JPBI, Biosfer JPB, and Bioedukatika. The three journals that are the object of this study have shown that they are pro-environmental. As for the three, JPBI can be considered as a journal that consistently publishes environmental themes, because this journal publishes the most articles on environmental themes. From the three journals, it can be seen that there are types of research that are dominantly used in environmental theme research, namely descriptive surveys, quasi-experiments and descriptive qualitative ones. In publications at JPBI, the topic of the environment is inseparable from education and the main subject of education is students. Environment is related to environmental education and environmental literacy. Meanwhile in the JPB Biosphere, environmental topics are also related to the themes of online learning or Blended/hybrid learning. On the other hand, in Bioedukatika the environmental theme is inseparable from the learning aspect. Based on the data, it can be seen that the main contribution of the three journals that are the object of this research is that teachers/lecturers are important actors in developing various abilities or skills of students/students in terms of the environment. Teachers are advised to apply various appropriate learning, which is oriented towards student active/student centered learning, by implementing the suggested learning models. One aspect that needs to be strengthened is the Adiwiyata Program which is the embodiment of green school-style schools in Indonesia. Exploration of local wisdom in various regions in Indonesia related to environmental wisdom is also still needed because it is positive for environmental strengthening.